A Comparative Analysis of the Structure of Tax Systems in Industrial Countries - Razin, Assaf (IMF Working Papers; Working Paper ;, 1993)
A methodology for computing effective average tax rates on factor incomes and consumption using OECD data from national accounts and revenue statistics is described and applied to construct time series of tax rates for the group of seven largest industrialized countries. These tax rates are compared with estimates of effective marginal tax rates obtained in other studies. The stylized facts that distinguish tax systems across countries are documented, and the co-movements between the tax rates and savings, investment, net exports, unemployment, and hours worked are also examined. The results of this analysis illustrate some of the potential implications of tax policies currently under consideration and suggest that the proposed tax rates are useful approximations to those faced by representative agents in dynamic macroeconomic models.